Central giant cell granuloma: A case report with review of literature - Kamala A Kamble; Sanketh S Guddad; Sujith S Guddad; Ashok Lingappa (Wolters Kluwer Medknow Publications, 2016)
Central giant cell granuloma (CGCG) is an uncommon, benign, and proliferative lesion of the jaw with an unknown etiology. It is considered widely to be a nonneoplastic lesion. The actual etiology of CGCG is still unclear, although inflammation, hemorrhage, and local trauma have all been suggested. The incidence in the general population is very low, and patients are generally younger than 30 years. The biologic behavior of CGCG of the jaw ranges from quiescent to aggressive with destructive expansion. Here, we report a case of CGCG in an 18-year-old female patient with review of literature.